State-Owned Enterprises Monopoly Based on Government Assignment According to Law Number 1 of 2025 on the Third Amendment to Law Number 19 of 2003 on State-Owned Enterprises - Kevin Iqbal Rizaldi (Journal of Social Research, 2025)
Special assignments to State-Owned Enterprises, as stipulated in Article 87C of Law Number 1 of 2025 concerning the Third Amendment to Law Number 19 of 2003 concerning State-Owned Enterprises, constitute an attributive right granted by law to the President of the Republic of Indonesia in carrying out his/her functions within the government, involving State-Owned Enterprises as entities specifically tasked with developing the national economy in specific business and industrial sectors. These special assignments can directly impact a particular industry, and while special assignments are a right vested in the President of the Republic of Indonesia, in practice, it is necessary to establish derivative regulations governing the procedures and clear units of value for implementing these special assignments. This is done to ensure that the government's efforts to develop the national economy are not hampered by issues of business monopoly practices, as stipulated in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition.